A combinatorial study of electrochemical anion intercalation into graphite. (6th August 2021) - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas D
Abstract: Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF 6 − ), perchlorate (ClO 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF 6 − are the most stable ones. These PF 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.